STRATEGI MENINGKATKAN KESADARAN HAK PRIVASI DALAM PENGGUNAAN LAYANAN ONLINE DALAM ERA DIGITAL - Wiraguna, Sidi Ahyar (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
In the growing digital age, the use of online services has become an integral part of daily life. The convenience and benefits offered by online services, there are also concerns about personal data privacy. Law No. 11 of 2008 on ITE article 26 paragraph 1: "the use of any information through electronic media concerning a person's personal data must be done with the consent of the person concerned." This rule is derived from Government Regulation No. 82/2012 and Government Regulation No. 71/2019. This article discusses strategies to raise awareness of privacy rights in the use of online services. This research focuses on the aspect of individuals' awareness of their data privacy when interacting with digital platforms. The first strategy is education and outreach on online privacy rights, which includes understanding the risks associated with sharing personal data online. The importance of privacy policy transparency and understanding how algorithms used by online platforms work are also highlighted. The second strategy is the development of software and tools that give users greater control over protecting their data. Innovations in technologies that enable end-to-end encryption, data permission management, and online activity monitoring can help individuals to be more active in protecting their privacy. The third strategy is strict oversight and regulation of data collection and use practices by online companies. This article details these efforts and explores how these strategies can be applied in various contexts. As such, it provides a comprehensive view of how to raise awareness of privacy rights in the use of online services in the digital age